Overcoming the challenges of drug development in platinum-resistant ovarian cancer - Eskander, Ramez N.; Moore, Kathleen N.; Monk, Bradley J.; Herzog, Thomas J.; Annunziata, Christina M.; O’Malley, David M.; Coleman, Robert L. (Frontiers in Oncology, 2023)
The definition of “platinum-resistant ovarian cancer” has evolved; it now also reflects cancers for which platinum treatment is no longer an option. Standard of care for platinum-resistant ovarian cancer is single-agent, non-platinum chemotherapy with or without bevacizumab, which produces modest response rates, with the greatest benefits achieved using weekly paclitaxel. Several recent phase 3 trials of pretreated patients with prior bevacizumab exposure failed to meet their primary efficacy endpoints, highlighting the challenge in improving clinical outcomes among these patients. Combination treatment with antiangiogenics has improved outcomes, whereas combination strategies with immune checkpoint inhibitors have yielded modest results. Despite extensive translational research, there has been a lack of reliable and established biomarkers that predict treatment response in platinum-resistant ovarian cancer. Additionally, in the platinum-resistant setting, implications for the time between the penultimate dose of platinum therapy and platinum retreatment remain an area of debate. Addressing the unmet need for an effective treatment in the platinum-resistant setting requires thoughtful clinical trial design based on a growing understanding of the disease. Recent cancer drug approvals highlight the value of incorporating molecular phenotypes to better define patients who are more likely to respond to novel therapies. Clinical trials designed per the Gynecologic Cancer InterGroup recommendations—which advocate against relying solely upon the platinum-free interval—will help advance our understanding of recurrent ovarian cancer response where platinum rechallenge in the platinum-resistant setting may be considered. The inclusion of biomarkers in clinical trials will improve patient stratification and potentially demonstrate correlations with biomarker expression and duration of response. With the efficacy of antibody-drug conjugates shown for the treatment of some solid and hematologic cancers, current trials are evaluating the use of various novel conjugates in the setting of platinum-resistant ovarian cancer. Emerging novel treatments coupled with combination trials and biomarker explorations offer encouraging results for potential strategies to improve response rates and prolong progression-free survival in this population with high unmet need. This review outlines existing data from contemporary clinical trials of patients with platinum-resistant ovarian cancer and suggests historical synthetic benchmarks for non-randomized trials.